La Russie de Vladimir Poutine et l’intégration économique de l’espace post-soviétique - Lilit Vardanyan (Études Arméniennes Contemporaines, 2013)
This article analyses Russian policy towards former Soviet republics. Having gained independence in 1991, they have been pursuing stronger ties and cooperation with western international organizations, such as NATO and the European Union. In contrast with this objective, the article examines political and strategic stakes of the current expansion of the Customs Union promoted by Russian diplomacy through direct involvement of President Vladimir Putin.